Dialogical Method in Islamic Education Based on Al-Faraby's Thoughts - Khairunnisa; Syahidin; Muhyi, Abdul; Iffah, Izzatul; Nur, Tya Shofarina M.; Jalal, M. Rifky Faisal (Universitas Pendidikan Ganesha, 2025)
The concept of education in Islamic tradition has undergone significant development through the thoughts of philosophers, one of whom is Al-Faraby. Al-Faraby education is a process that aims to shape individuals into ethical and intelligent human beings. Al-Faraby believes that dialogic methods in education are essential to encourage student engagement and critical thinking. The purpose of this study is to analyze the dialogic methodology in Islamic education based on Al-Faraby's thoughts. The research method used is the literature review method. In carrying out a literature review, structured steps must be followed, starting from the formulation of research questions to the selection of relevant sources. Through a critical analysis of existing sources, researchers can identify the methodology that has been used, as well as the results obtained from previous studies. The results of the study show that Al-Faraby emphasizes that education should be lifelong, and the dialogic method supports this principle by encouraging students to continue learning and discussing outside the formal environment. The dialogic method not only increases student engagement in the learning process but also encourages the development of critical thinking skills, social skills, and a deeper understanding of Islamic values. Thus, the application of dialogical methods in Islamic education can produce a generation that is not only academically intelligent but also ethical and responsible.